Cellular mechanisms regulating non-haemostatic plasmin generation. (April 2002) - Bass, R.; Ellis, V.
Abstract : A variety of proteases have the potential to degrade the extracellular matrix (ECM), thereby influencing the behaviour of cells by removing physical barriers to cell migration, altering cell-ECM interactions or releasing ECM-associated growth factors. The plasminogen activation system of serine proteases is particularly implicated in this pericellular proteolysis and is involved in pathologies ranging from cancer invasion and metastasis to fibroproliferative vascular disorders and neurodegeneration. A central mechanism for regulating plasmin generation is through the binding of the two plasminogen activators to specific cellular receptors: urokinase-type plasminogen activator to the glycolipid-anchored membrane protein uPAR, and tissue plasminogen activator to a type-II transmembrane protein recently identified on vascular smooth muscle cells. These binary complexes interact with membrane-associated plasminogen to form higher order activation complexes that greatly reduce the K m for plasminogen activation and, in some cases, protect the proteases from their cognate serpin inhibitors. Various other proteins that are involved in cell adhesion and migration also interact with these complexes, modulating the activity of this efficient and spatially restricted proteolytic system. Recent observations demonstrate that certain forms of the prion protein can stimulate tissue plasminogen activator-catalysed plasminogen activation, which raises the possibility that these proteases may also have a role in the pathogenesis of the transmissible spongiform encephalopathies.